Slavery In Postcolonial Africa: The Role Of Technology - Stella Bassey Esirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
Technology is a two-edged sword. It is at once negative and positive in its constitution. It could be used for good; it could also be used for evil. It use therefore, is dependent on the morality of the mind that employs it. In the past and sadly, presently it has been used to foster slavery in Africa. I however believe that technology could be made to make a positive turn to aid the total abolishment of all forms of slavery in postcolonial Africa. Slavery rides on factors like poverty, illiteracy, insecurity, lack of infrastructures etc, which abound in Africa. Slavery would end if these factors are removed. Thus, if conditions are made possible for comfortable living, then slave masters would run short of slaves and would be forced to look for alternative to slaves. However, the best way to improve the living conditions of a people is through technology. The work therefore, urges the developed world to be generous to Africa by way of technology transfer. One way to do this is through biffing up its indigenous technologies with foreign technologies through technology transfer. Another way to do this, which is the proper responsibility of African government themselves, is to stop the brain-drain wave which is presently moving with a very strong current towards the West and the South. When the best brains are retained in the continent, there is a likelihood that technology would grow in Africa and consequently Africa would know development. When this is so, slavery would lose its roots and would therefore wither off.